Impact of pirimiphos-methyl and cold temperatures on arthropod populations in stored wheat - White, N.D.G.; Jayas, D.S.; Sinha, R.N. (Phytoprotection, 1994)
The insecticide pirimiphos-methyl applied at a mean concentration of 6.4 mg a.i. kg 1 to 5t of wheat (Triticum aestivum) in a farm granary in southern Manitoba remained active over 24 mo. Most insects and mites in the treated grain could not survive except a psocid, Liposcelis sp., and the mites Tarsonemus granarius and Aeroglyphus robustus, and their populations were sharply reduced relative to those in a bulk of untreated wheat. Insecticide residues at a 1-m depth decreased ca. 52% in 12 mo from 8.1 mg kg-1 to 4.0 mg kg-1, then remained constant until 24 mo. Grain moisture content (MC) at this depth was consistently higher (over 14% MC) than at the top of the wheat bulk where residues remained near 4.5 mg kg-1 over 24 mo. Grain temperatures fluctuated from summer maxima near 23°C to winter minima near -40°C at the bulk surface. Bioassay of treated wheat with adult Tribolium castaneum after 24 mo of storage resulted in about 80% mortality. Populations of T castaneum or Rhyzopertha dominica introduced into 5 t of untreated wheat did not become established; small populations of Cryptolestes ferrugineus were established but were eliminated by winter cold. Populations of Liposcelis sp. and the mites A. robustus, T. granarius, Blattisocius keegani and Cheyletus eruditus were highest in late summer and autumn. Seed germination and microflora were not directly affected by pirimiphos-methyl. The slow rate of degradation of this insecticide in grain would prevent communities of arthropods from developing to the same extent as in an untreated stored-wheat ecosystem over 24 mo.